Oxidative stress in Alzheimer's disease: Primary villain or physiological by-product?. (1st July 2013) - Sutherland, Greg T; Chami, Belal; Youssef, Priscilla; Witting, Paul K
Abstract : The prevalence of Alzheimer's disease (AD) is increasing rapidly worldwide due to an ageing population and largely ineffective treatments. In AD cognitive decline is due to progressive neuron loss that begins in the medial temporal lobe and spreads through many brain regions. Despite intense research the pathogenesis of the common sporadic form of AD remains largely unknown. The popular amyloid cascade hypothesis suggests that the accumulation of soluble oligomers of beta amyloid peptides (Aβ) initiates a series of events that cause neuronal loss. Among their putative toxic effects, Aβ oligomers are thought to act as pro-oxidants combining with redox-active metals to produce excessive reactive oxygen and nitrogen species. However, to date the experimental therapies that reduce Aβ load in AD have failed to halt cognitive decline. Another hypothesis proposed by the late Mark Smith and colleagues is that oxidative stress, rather than Aβ, precipitates the pathogenesis of AD. That is, Aβ and microtubule-associated protein tau are upregulated to address the redox imbalance in the AD brain. As the disease progresses, excess Aβ and tau oligomerise to further accelerate the disease process. Here, we discuss redox balance in the human brain and how this balance is affected by ageing. We then discuss where oxidative stress is most likely to act in the disease process and the potential for intervention to reduce its effects.